IMPLEMENTASI KEBIJAKAN PEMERINTAH ACEH DALAM MENURUNKAN ANGKA KEMISKINAN PROVINSI ACEH TAHUN 2018-2021 - Yusril Yudi Safaat; Aminah Aminah; Khalisni Khalisni (Journal of Political Sphere, 2022)
ABSTRACTAceh's poverty rate remains high, suggesting that many people still cannot afford to meet their basic needs. The government of Aceh has implemented policies aimed to alleviate poverty in Aceh, one of which is through a transmigration program in Sigulai, a village located in Simeulue Regency. The transmigration program in this location is expected to contribute to reducing the number of poor people in Aceh. However, despite the effort, the rates of poverty remain high. Based on this condition, this study aimed to examine the policy implementation and problems faced in its implementation regarding the transmigration program in Sigulai from 2017 to 2020. This study employed Meter and Horn's policy implementation theory and the concept of poverty. This study was qualitative. The data were collected using interviews, observation, and literature study. The data were analyzed through Triangulation, Reduction, and Concluding. The results of this study suggest that the process of implementing transmigration development is not being carried out as planned in the policy. Implementation restrictions are due to the implementers' dispositions and inexperience at the policy formulation stage. Based on the results of this study, the researcher suggests that the Simeulue district office prevent fraud and that those responsible for it adopt appropriate rules for future transmigration development.Keywords: policy, poverty alleviation, transmigration